По щучьему веленью: русские народные сказки / художник Виталий Кастальский - Кастальский Виталий Эрикович (Серия " Книжка-малышка", 2012)
Экземпляры: Ф20 (20211127) / Инвентарный номер: 62076 / Цена: 23.00 / Сис.шифр: Д / Авт.знак: П 41 / ГРНТИ: 17.82.93 / ББК: 82.3(2Рос=Рус)мл